Alternativas de manejo do capim-tifton 85 sob pastejo por cabras leiteiras em lotação rotativa - Cutrim Junior, José Antônio Alves (2011)
Was conducted this study to evaluate management alternatives grazing Bermuda grass (Tifton 85), grazing by dairy goats in intermittent stocking, carried at Embrapa Goats and Sheeps in Ceara (3º40’42” latitude, 40º16’50.5” longitude and 79 m high). The management were combinations of residual height and nitrogen doses (N), consisted of Conventional (height 10 cm and residual without fertilization), Lightweight (20 cm residual height and unfertilized), Moderate (residual height 20 cm and fertilizer equivalent to 300 kg N/ha x year) and Intensive (height 10 cm and residual fertilizer equivalent to 600 kg N / ha x year). A randomized design was used with repeated measures over time (grazing cycles), in two periods of the year, with four replicates on management. There were four replicates per management throughout the year for characteristics of the pasture. For animal characteristics were four replications during the rainy period and five repetitions during the dry period. Was established the entry criteria of the animals at light intercepted by the canopy, where it achieved 95% of photosynthetic active radiation (PAR). The grazing period consisted of four days. Among the characteristics of the biomass flow measured the leaf elongation rate (LER) was greatly influenced by managements (P<0,05), with less elongation on Light management during the dry period under irrigation (1.54 cm/day x tiller), period wich had lower average LER in all managements. The rates of leaf senescence earlier (LSRe), posterior (LSRp) and total leaf senescence (TLS) were higher (P<0,05) during the rainy season (1.04, 0.55 and 1.59 cm/day x tiller, respectively). The higher leaf appearance rate (LAR) was observed in the Intensive management during the dry season under irrigation with 0.38 leaves/day. Among the structural features of the tiller density population (TDP) was higher during the dry season under irrigation in all managements, enhanced by nitrogen fertilizer due to higher TDP in the Intensive management in this period. The dry mass total herbage (DMTH) and dry mass green herbage (DMGH) were higher in Moderate management of the average periods of the year with 7292 and 5118 kg/ha, respectively. Was also this mentioned in these residual mass provided. Along with Moderate management, the Intensive management has a high dry mass green leaves (1849 kg/ha – DMGL) but a lower dry mass green stem (2541 kg/ha – DMGS), which favored greater leaf/stem relationship for this management, also showed in residual condition. The weight of the animals during the rainy period was decreasing unlike than the score that presented little variation. Was effect of managements under weight and body scores of animals in dry period under irrigation, with less weight for the animals in Intensive management. There was a great fluctuation in weight of animals during the dry period under irrigation, as well as for the score, but this has been a growing from the month of December. There was a high frequency of grade Famacha® 3 along the dry period under irrigation, having started with immediately increased rainfall. During the dry period under irrigation control worms Famacha® method was more effective. There was also a large number of deworming Moderate for management in the rainy period, showing the high incidence of parasitism occurred reflecting the lower body condition score of the animals of this management. Was higher stocking rate for Intensive management (P<0.05) both in the rainy period and during the dry period under irrigation. The management without fertilizer had a lower stocking rate. The total milk yield and lactation length in the rainy period were higher for Conventional management, unlike in the dry period under irrigation was not different managements for this feature. As for productivity in all characteristics, the Intensive management was superior to other management. In what refers to individual production, Conventional management presented values above other managements in both rainy and dry period under irrigated with an average of 0.782 and 1.453 kg of milk/goat x day, for the periods, respectively. The lactation curve in the rainy period showed up short in all management, with peak lactation in the first week of lactation and production slump soon after. In the dry period under irrigation the lactation curve was more extensive, with peak times between the different managements, with higher peak lactation Light management with 2243 kg of milk/goat x day. Was observed higher MLR in the Intensive management both in systems for 1 and 3 hectares, without discarding the milk with hand milking. With mechanical milking there was a decrease in monthly income in all simulations. The Intensive management in areas 1 and 3 hectares with hand milking show with good economic indicators. Goats Milk production in Bermuda grass (Tifton 85) pasture appears to be more efficient in Intensive management conditions of the pasture maximized by irrigation during the dry period of the year due to improved environmental conditions of grazing and lower problems with worms.